KEANEKARAGAMAN JENIS IKAN DARI EKOSISTEM MANGROVE DI DESA PAGATAN BESAR, KABUPATEN TANAH LAUT, PROVINSI KALIMANTAN SELATAN - Kadarsah, Anang; Turrahmah, Maulida; Gafur, Abdul (Teknosains: Media Informasi Sains dan Teknologi, 2020)
The existence of mangrove ecosystems in Pagatan Besar Village of Tanah Laut Regency provides benefits for a variety of fish and the surrounding waters. This study aims to identify the diversity of fish species from mangrove and coastal ecosystems in Pagatan Besar Village, Tanah Laut Regency. The research method use a survey methods and fishing use a purposive sampling based on the differences of habitat conditions. The parameters was measured including fish species, density, diversity index, evenness index, and similarity index. The results showed that found as many as 18 species of fish from the mangrove forest and even more from the coast (20 types). Belama fish (Argyrosomus sp.; Scienidae) is the type of fish most commonly found in the mangrove forests (31.31%) while on the coast are Klepes fish (Amblygaster leiogaster: Clupidae) with the value is 44.96%. The average abundance of fish from the mangrove forest is 66 individuals/m2 of fish nets) smaller than coastal fishing (94.17 individuals/m2 of fish nets). Diversity index of fish from the mangrove forest was 2.12 and from the coast is smaller (1.68). Evenness Index from mangrove forests is higher (1.68) compared to the coast (1.29). And the similarity index number of fish species in mangrove forests and coastal areas was 58.3%.